Evaluating outcomes of a three-year case management program for mothers with prenatal substance use according to race/ethnicity, Washington State, 2006-2017 - Susan A. Stoner; J. Christopher Graham; Therese M. Grant (BMC, 2023)
Abstract Background Well-designed public health interventions ideally aspire to reduce health disparities between racial and ethnic groups. Yet, there remains virtually no research examining racial/ethnic disparities in interventions for marginalized perinatal populations with substance use disorders (SUD). We sought to examine whether there were racial/ethnic differences at intake, in retention, and in program outcomes among pregnant or postpartum women with prenatal substance use enrolled in a three-year intensive case management intervention. We hypothesized that: (1) at baseline, numerous racial/ethnic disparities in well-being, health, and health care would be observed, and (2) after the three-year intervention few racial/ethnic disparities in maternal and child health and welfare would be found. Methods We used self-reported data from 3,165 women aged 18 to 45 years enrolled in the Parent-Child Assistance Program in Washington State between May 10, 2006, and September 21, 2017. We used Fisher-Freeman-Halton Exact Tests and t-tests to compare racial/ethnic groups at program enrollment and exit and logistic regression to examine likelihood of completing the intervention by group, controlling for other factors. Results Despite numerous racial/ethnic differences at enrollment, there were no such differences in outcomes among those who finished the program and completed an exit interview. Different racial/ethnic groups received comparable case manager time. American Indians/Alaska Natives were less likely to finish the program (Adjusted Odds = 0.66). Conclusions Participants who finished the program achieved comparable outcomes regardless of race/ethnicity. More work is needed to understand why American Indian/Alaska Native women were less likely than the others to finish the program and to close this service gap.